The Post-verbal Effect of Negators in Mongolian Contradictory Negations Provides Support for the Fusion Model - Xu, Qinghong; Zhang, Shujun; Li, Jie; Wu, Baizhou; Qiu, Helin; Qilimuge (Frontiers in Psychology, 2021)
There are two contending models regarding the processing of negation: the fusion model and the schema-plus-tag model. Most previous studies have centered on negation in languages such as English and Mandarin, where negators are positioned before predicates. Mongolian, quite uniquely, is a language whose negators are post-verbal, making them natural replicas of the schema-plus-tag model. The present study aims to investigate the representation process of Mongolian contradictory negative sentences to shed light on the debate between the models, meanwhile verifying the post-verbal effect of negators. A series of experiments using the sentence–picture verification paradigm supports the fusion model: (i) Mongolian contradictory negative sentences were processed by representing the actual conditions rather than the negated state of affairs at 250 ISI (interstimulus interval of 250 ms), and (ii) despite the fact that a post-verbal effect of negators was measured at 250 ISI when Mongolian and Mandarin negative sentences were compared, Mongolian–Mandarin bilinguals adopted the same representational strategy for contradictory negation in both languages.